Nanometer Co2O3 / Fe3O4 composite PMS activation catalyst as well as preparation method and application thereof

By loading nanoCo2O3 and Fe3O4 in the biocarbon material chitosan, and introducing pyridine N and thiophene S to form a nanoCo2O3/Fe3O4 composite PMS activation catalyst with core-shell structure, the problem of low efficiency of existing catalysts is solved and high efficiency is achieved Catalytic and magnetic recovery, suitable for industrial water treatment.

CN119140140AActive Publication Date: 2024-12-17CNBM RESEARCH INSTITUTE FOR ADVANCED GLASS MATERIALS GROUP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411120810.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2024-12-17
Estimated Expiration
2044-08-15

AI Technical Summary

Technical Problem

The existing Cu2O/CoFe2O4 magnetic composite catalysts have low catalytic efficiency and cannot meet the needs of industrial-scale applications.

Method used

Using nano-Co2O3/Fe3O4 composite PMS activation catalyst, by loading Fe3O4 nanoparticles and Co2O3 nanoparticles in the biocarbon material chitosan, the electronic structure is adjusted, the surfactant site is increased, and pyridine N and modified chitosan are introduced. Thiophene S, forming a core-shell structure, enhances the ability to catalytically activate PMS.

Benefits of technology

The activation efficiency and magnetism of the catalyst are significantly improved, the magnetic separation and recovery of the catalyst is realized, the cost of use is reduced, and excellent catalytic performance and stability are shown in water treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140140A_ABST
    Figure CN119140140A_ABST
Patent Text Reader

Abstract

The invention discloses a nano Co2O3 / Fe3O4 composite PMS activation catalyst as well as a preparation method and application thereof, and belongs to the technical field of nano catalytic materials. Comprising the following raw materials in parts by weight: 18-36 parts of modified chitosan, 100-200 parts of a citric acid solution, 3-7 parts of cobalt chloride hexahydrate and 4-8 parts of ferric chloride hexahydrate. According to the prepared catalyst, Fe3O4 and Co2O3 nanoparticles are loaded in a biological carbon material, so that the activation of the bimetal catalytic PMS is better; the magnetism of Fe is beneficial to recovery of the catalyst, so that the cost is reduced; chitosan is modified, so that the PMS activation efficiency of the catalyst is enhanced; therefore, the prepared catalyst takes chitosan as a base material, is loaded with Fe and Co and is doped with N and S, has a synergistic effect, is extremely high in PMS activation efficiency, can be recycled through magnetic force, is low in cost and has a remarkable application value in the water treatment industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano-catalytic materials, and in particular relates to a nano-Co2O3 / Fe3O4 composite PMS activated catalyst and a preparation method and application thereof. Background Art

[0002] In water pollution control, persulfate catalytic treatment of sewage has attracted much attention and research due to its advantages of high efficiency, rapidity, energy saving and environmental protection. This technology produces highly active free radicals such as sulfate radicals (SO4· - ) or oxygen free radicals (·OH), which have strong oxidizing ability and can effectively decompose organic matter in water, including organic solvents, color substances and difficult-to-degrade organic matter. Its rapid reaction speed allows sewage to be treated in a short time, improving the treatment efficiency, and is especially suitable for situations that require rapid treatment. In addition, the active free radicals generated can oxidize organic matter in water without the need to add additional oxygen or oxidants, thereby reducing treatment costs. Persulfate catalytic sewage treatment technology is suitable for various types of organic wastewater, including industrial wastewater, rural sewage and domestic sewage, and has a wide range of applicability. Since the operation is carried out at room temperature and no high temperature conditions are required, energy consumption and operating costs are reduced. The reaction products produced by this technology are usually non-toxic and harmless substances that will not cause secondary pollution to the environment. In the future, through continuous research and improvement of water pollution control technology, persulfate catalytic sewage treatment technology is expected to be further optimized and improved.

[0003] Patent CN114054028A discloses a method for preparing a Cu2O / CoFe2O4 magnetic composite catalyst, comprising the following steps: ultrasonically dispersing cobalt ferrite in distilled water, adding a certain amount of copper sulfate solution with a concentration of 0.5 mol / L after ultrasonication, and stirring at room temperature for 60 min; dripping sodium hydroxide solution drop by drop under continuous stirring, and then dripping ascorbic acid solution drop by drop; stirring and reacting at 20°C for 2h to obtain a cuprous oxide / cobalt ferrite dispersion; filtering the dispersion and repeatedly washing it with anhydrous ethanol and distilled water for 3-5 times to remove impurities, and drying it at 80°C to obtain a Cu2O / CoFe2O4 magnetic composite catalyst. The process is simple, and the prepared Cu2O / CoFe2O4 magnetic composite catalyst has high purity, strong stability, convenient recovery, and can be recycled. However, the catalytic efficiency of the catalyst is low and cannot meet large-scale industrial applications. Therefore, it is urgent to solve the above problems to meet the higher requirements in the field of nanocatalytic material technology. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a nano Co2O3 / Fe3O4 composite PMS activated catalyst and a preparation method and application thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A method for preparing a nano Co2O3 / Fe3O4 composite PMS activated catalyst comprises the following steps:

[0007] A1. Dissolve the modified chitosan in a citric acid solution and stir to mix evenly, add cobalt chloride hexahydrate and ferric chloride hexahydrate, and continue stirring to mix to obtain a mixed solution;

[0008] A2, placing the mixed solution obtained in step A1 in a constant temperature water bath, stirring until the liquid is evaporated, and then scraping out the sample and drying it to obtain a mixed solid;

[0009] A3. Add the mixed solid obtained in step A2 into a porcelain boat, place the whole in a tube furnace, introduce inert gas, and calcine. After the calcination is completed, wait for the tube furnace to cool naturally to room temperature, soak the product in a hydrochloric acid solution for stirring and pickling, then wash with ultrapure water for multiple times until the filtrate is neutral, then wash with anhydrous ethanol for 3-4 times, and finally dry to obtain a nano Co2O3 / Fe3O4 composite PMS activated catalyst.

[0010] Furthermore, the raw materials are calculated in parts by weight as follows: 18-36 parts of modified chitosan, 100-200 parts of citric acid solution, 3-7 parts of cobalt chloride hexahydrate, and 4-8 parts of ferric chloride hexahydrate.

[0011] Furthermore, the drying condition in step A2 is drying in a vacuum oven at 80-100° C. for 6-12 h.

[0012] Furthermore, the inert gas in step A3 is one of nitrogen and argon.

[0013] Furthermore, the calcination conditions in step A3 are to increase the temperature to 600-800° C. at a heating rate of 2° C. / min and keep the temperature for 2-5 hours.

[0014] Furthermore, the drying condition in step A3 is drying in a vacuum oven at 80-100° C. for 6-12 h.

[0015] By loading Fe3O4 nanoparticles and Co2O3 nanoparticles in biochar materials (chitosan), the bimetallic can adjust the electronic structure and achieve better activation efficiency than a single metal. It can effectively prevent the catalyst from agglomerating while expanding the specific surface area and increasing the surface active sites, which can greatly improve the catalytic efficiency. In addition, the introduction of Fe can also improve the graphitization degree of biochar materials, form a core-shell structure, strengthen electron transfer, and enhance the ability to activate PMS. Moreover, the magnetic properties of Fe3O4 and Co2O3 are conducive to the magnetic separation and recovery of the catalyst in the solution, reducing the cost of use.

[0016] Furthermore, the modified chitosan is prepared by the following steps:

[0017] S1. In a three-necked flask equipped with a stirring device, 2,5-thiophene dicarboxylic acid, 4-aminopyridine, dicyclohexylcarbodiimide (DCC, dehydrating agent) and toluene were stirred and mixed uniformly, and then placed in a water bath at 55°C and heated in a water bath for 6 hours. After the reaction was completed, the mixture was filtered, and the solvent was removed by vacuum distillation. The mixture was then purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate in a volume ratio of 2:3), and the eluent was removed by rotary evaporation to obtain a modifier; the ratio of 2,5-thiophene dicarboxylic acid, 4-aminopyridine, dicyclohexylcarbodiimide and toluene was 18.4 g:9.4 g:20.6 g:100 mL;

[0018] Under the action of a dehydrating agent, 2,5-thiophene dicarboxylic acid and 4-aminopyridine undergo an amidation reaction. By controlling the molar ratio of the two to be close to 1:1 and a slight excess of 2,5-thiophene dicarboxylic acid, only one carboxyl group on 2,5-thiophene dicarboxylic acid participates in the reaction to obtain a modifier. The specific reaction process is as follows:

[0019]

[0020] S2. Add chitosan to a mixed solution of acetic acid and toluene (the mass fraction of acetic acid is 24%), stir until completely dissolved, then add a modifier and dicyclohexylcarbodiimide, control the reaction temperature to 60°C, keep the reaction warm for 12 hours, and after the reaction is completed, perform vacuum distillation, wash with ethanol and water in turn, and dry in an oven to obtain modified chitosan; the ratio of the mixed solution of acetic acid and toluene, chitosan, modifier, and dicyclohexylcarbodiimide is 100mL:1g:2.4g:15mL;

[0021] Under the action of dicyclohexylcarbodiimide, the carboxyl group on the modifier reacts with the amino group on chitosan to obtain modified chitosan.

[0022] Chitosan is a biocarbon material, a carbon-rich substance with wide sources, eco-friendly, low cost and renewability. It can be formed into a porous material by calcination, and the structural defects produced by calcination are helpful to activate PMS. By modifying chitosan, pyridine and thiophene structures are grafted on chitosan, in which the lone electron pair of pyridine N can react with sp 2 The rich free-flowing π electrons in C undergo conjugation and induce higher catalytic activity. Pyridine N can also form Fe-NX active sites with Fe, further enhancing the catalytic activity. In addition, the introduced thiophene S can not only enhance the electron density and asymmetric spin of the biocarbon material and promote the adsorption of PMS, but also serve as an active site for PMS, further enhancing the catalytic activity.

[0023] Beneficial effects of the present invention:

[0024] 1. The catalyst prepared by the present invention loads Fe3O4 nanoparticles and Co2O3 nanoparticles in biocarbon materials, so that the activation of bimetallic catalytic PMS is more effective; and the magnetic properties of Fe3O4 and Co2O3 are conducive to the magnetic separation and recovery of the catalyst in the solution, thereby reducing the use cost;

[0025] 2. By modifying chitosan and introducing pyridine N and thiophene S, the active sites of the catalyst were significantly improved, and the activation efficiency of the catalyst for PMS was enhanced;

[0026] Therefore, the catalyst prepared by the present invention uses chitosan as a substrate, has low cost, and has a synergistic effect by loading Fe and Co and doping N and S, has a very high activation efficiency for PMS, and can be recovered by magnetic force, further reducing costs, and has significant application value in the water treatment industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The present invention will be further described below in conjunction with the accompanying drawings.

[0028] Figure 1 This is a SEM image of the nano-Co2O3 / Fe3O4 composite PMS activated catalyst prepared in Example 1 of the present invention.

[0029] Figure 2 This is a SEM image of the nano-Co2O3 / Fe3O4 composite PMS activated catalyst prepared in Example 2 of the present invention.

[0030] Figure 3 This is a SEM image of the nano-Co2O3 / Fe3O4 composite PMS activated catalyst prepared in Example 3 of the present invention.

[0031] Figure 4 This is the VSM hysteresis loop diagram of the nano-Co2O3 / Fe3O4 composite PMS activated catalyst prepared in Example 1 of the present invention.

[0032] Figure 5 This is a photo of the nano-Co2O3 / Fe3O4 composite PMS activated catalyst prepared in Example 1 of the present invention being adsorbed on a magnet.

[0033] Figure 6 This is the degradation curve of R6G of the Co2O3 / Fe3O4 composite PMS activated catalyst prepared in Examples 1-5 of the present invention.

[0034] Figure 7 This is the degradation efficiency curve of R6G when the Co2O3 / Fe3O4 composite PMS activated catalyst prepared in Example 1 of the present invention is recycled. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Example 1

[0037] A1. Dissolve 36 g of modified chitosan in 200 g of citric acid solution (mass fraction 12%) and stir for 2 h to mix evenly. Add 7 g of cobalt chloride hexahydrate and 8 g of ferric chloride hexahydrate and continue stirring for 2 h to obtain a mixed solution.

[0038] A2, placing the mixed solution obtained in step A1 in a constant temperature water bath at 80°C, stirring until the liquid is evaporated, then scraping out a sample and drying it in a vacuum oven at 100°C for 12 hours to obtain a mixed solid;

[0039] A3, adding the mixed solid obtained in step A2 into a porcelain boat, and placing the whole in a tube furnace, and introducing nitrogen, heating to 800°C at a heating rate of 2°C / min, calcining for 5 hours, and after the calcination is completed, the tube furnace is naturally cooled to room temperature, and the product is immersed in a hydrochloric acid solution (mass fraction 12%) for stirring and pickling, and then washed with ultrapure water for several times until the filtrate is neutral, and then washed with anhydrous ethanol for 4 times, and finally dried in a vacuum oven at 100°C for 12 hours to obtain a nano Co2O3 / Fe3O4 composite PMS activated catalyst;

[0040] Wherein, the modified chitosan is prepared by the following steps:

[0041] S1. In a three-necked flask equipped with a stirring device, 18.4 g of 2,5-thiophene dicarboxylic acid, 9.4 g of 4-aminopyridine, 20.6 g of dicyclohexylcarbodiimide and 100 mL of toluene were stirred and mixed uniformly, and then placed in a water bath at 55° C. and heated in a water bath for 6 h. After the reaction was completed, the mixture was filtered, and the solvent was removed by distillation under reduced pressure. The mixture was purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 2:3), and the eluent was removed by rotary evaporation to obtain a modifier;

[0042] S2. Add 1 g of chitosan to a mixed solution of 100 mL of acetic acid and toluene (the mass fraction of acetic acid is 24%), stir until completely dissolved, then add 2.4 g of a modifier and 15 mL of dicyclohexylcarbodiimide, control the reaction temperature to 60°C, keep the reaction warm for 12 hours, and after the reaction is complete, distill under reduced pressure, wash with ethanol and water in turn, and dry in an oven to obtain modified chitosan.

[0043] Embodiment 1 is described with reference to the accompanying drawings. Figure 1 As shown in the figure, it can be clearly seen that the sample is granular and has good dispersion; Figure 4 As shown in the figure, it can be seen that the magnetic properties of the sample are as high as 29.8emu / g; the actual photo of magnet adsorption is shown in Figure 5 As shown in the figure, it can be clearly seen that the catalyst in the centrifuge tube is firmly adsorbed on the upper part of the centrifuge tube by the magnet and does not fall off, which shows that it has strong magnetism, which is convenient for recycling; the degradation rate changes after 5 cycles are as follows Figure 7 As shown in the figure, it can be seen that after five cycles of use, although the 20-min degradation rate of the catalyst for R6G has decreased, it can still reach 93.2%, indicating that the catalyst has good stability and can be recycled and reused, which can reduce the cost of use.

[0044] Example 2

[0045] A1. Dissolve 20 g of modified chitosan in 175 g of citric acid solution (mass fraction 12%) and stir for 1 h to mix evenly. Add 6 g of cobalt chloride hexahydrate and 7 g of ferric chloride hexahydrate and continue stirring for 1 h to obtain a mixed solution.

[0046] A2, placing the mixed solution obtained in step A1 in a constant temperature water bath at 80°C, stirring until the liquid is evaporated, then scraping out a sample and drying it in a vacuum oven at 100°C for 12 hours to obtain a mixed solid;

[0047] A3, adding the mixed solid obtained in step A2 into a porcelain boat, and placing the whole in a tube furnace, and introducing nitrogen, heating to 750°C at a heating rate of 2°C / min, calcining for 4 hours, after the calcination is completed, waiting for the tube furnace to cool naturally to room temperature, soaking the product in a hydrochloric acid solution (mass fraction 12%) for stirring and pickling, then washing with ultrapure water for several times until the filtrate is neutral, and then washing with anhydrous ethanol for 4 times, and finally drying in a vacuum oven at 100°C for 12 hours to obtain a nano Co2O3 / Fe3O4 composite PMS activated catalyst;

[0048] Wherein, the modified chitosan is prepared by the following steps:

[0049] S1. In a three-necked flask equipped with a stirring device, 18.4 g of 2,5-thiophene dicarboxylic acid, 9.4 g of 4-aminopyridine, 20.6 g of dicyclohexylcarbodiimide and 100 mL of toluene were stirred and mixed uniformly, and then placed in a water bath at 55° C. and heated in a water bath for 6 h. After the reaction was completed, the mixture was filtered, and the solvent was removed by distillation under reduced pressure. The mixture was purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 2:3), and the eluent was removed by rotary evaporation to obtain a modifier;

[0050] S2. Add 1 g of chitosan to a mixed solution of 100 mL of acetic acid and toluene (the mass fraction of acetic acid is 24%), stir until completely dissolved, then add 2.4 g of a modifier and 15 mL of dicyclohexylcarbodiimide, control the reaction temperature to 60°C, keep the reaction warm for 12 hours, and after the reaction is complete, distill under reduced pressure, wash with ethanol and water in turn, and dry in an oven to obtain modified chitosan.

[0051] like Figure 2 As shown, it can be clearly seen from the figure that the sample is granular and the hybridization effect is good.

[0052] Example 3

[0053] A1. Dissolve 24 g of modified chitosan in 150 g of citric acid solution (mass fraction 12%) and stir for 1 h to mix evenly. Add 5 g of cobalt chloride hexahydrate and 6 g of ferric chloride hexahydrate and continue stirring for 2 h to obtain a mixed solution.

[0054] A2, placing the mixed solution obtained in step A1 in a constant temperature water bath at 80°C, stirring until the liquid is evaporated, then scraping out a sample and drying it in a vacuum oven at 100°C for 12 hours to obtain a mixed solid;

[0055] A3, adding the mixed solid obtained in step A2 into a porcelain boat, and placing the whole in a tube furnace, and introducing argon gas, heating to 700°C at a heating rate of 2°C / min, calcining for 4 hours, and after the calcination is completed, the tube furnace is naturally cooled to room temperature, and the product is immersed in a hydrochloric acid solution (mass fraction 12%) for stirring and pickling, and then washed with ultrapure water for several times until the filtrate is neutral, and then washed with anhydrous ethanol for 3-4 times, and finally dried in a vacuum oven at 100°C for 12 hours to obtain a nano Co2O3 / Fe3O4 composite PMS activated catalyst;

[0056] Wherein, the modified chitosan is prepared by the following steps:

[0057] S1. In a three-necked flask equipped with a stirring device, 18.4 g of 2,5-thiophene dicarboxylic acid, 9.4 g of 4-aminopyridine, 20.6 g of dicyclohexylcarbodiimide and 100 mL of toluene were stirred and mixed uniformly, and then placed in a water bath at 55° C. and heated in a water bath for 6 h. After the reaction was completed, the mixture was filtered, and the solvent was removed by distillation under reduced pressure. The mixture was purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 2:3), and the eluent was removed by rotary evaporation to obtain a modifier;

[0058] S2. Add 1 g of chitosan to a mixed solution of 100 mL of acetic acid and toluene (the mass fraction of acetic acid is 24%), stir until completely dissolved, then add 2.4 g of a modifier and 15 mL of dicyclohexylcarbodiimide, control the reaction temperature to 60°C, keep the reaction warm for 12 hours, and after the reaction is complete, distill under reduced pressure, wash with ethanol and water in turn, and dry in an oven to obtain modified chitosan.

[0059] like Figure 3 As shown, it can be clearly seen from the figure that the sample is granular and the hybridization effect is good.

[0060] Example 4

[0061] A1. Dissolve 20 g of modified chitosan in 125 g of citric acid solution (mass fraction 12%) and stir for 1 h to mix evenly. Add 4 g of cobalt chloride hexahydrate and 5 g of ferric chloride hexahydrate and continue stirring for 1 h to obtain a mixed solution.

[0062] A2, placing the mixed solution obtained in step A1 in a constant temperature water bath at 80°C, stirring until the liquid is evaporated, then scraping out a sample and drying it in a vacuum oven at 80°C for 6 hours to obtain a mixed solid;

[0063] A3, adding the mixed solid obtained in step A2 into a porcelain boat, and placing the whole in a tube furnace, and passing argon gas, heating to 650°C at a heating rate of 2°C / min, calcining for 2h, after the calcination is completed, waiting for the tube furnace to cool naturally to room temperature, soaking the product in a hydrochloric acid solution (mass fraction 12%) for stirring and pickling, then washing with ultrapure water for several times until the filtrate is neutral, and then washing with anhydrous ethanol for 3 times, and finally drying in a vacuum oven at 80°C for 6h to obtain a nano-Co2O3 / Fe3O4 composite PMS activated catalyst;

[0064] Wherein, the modified chitosan is prepared by the following steps:

[0065] S1. In a three-necked flask equipped with a stirring device, 18.4 g of 2,5-thiophene dicarboxylic acid, 9.4 g of 4-aminopyridine, 20.6 g of dicyclohexylcarbodiimide and 100 mL of toluene were stirred and mixed uniformly, and then placed in a water bath at 55° C. and heated in a water bath for 6 h. After the reaction was completed, the mixture was filtered, and the solvent was removed by distillation under reduced pressure. The mixture was purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 2:3), and the eluent was removed by rotary evaporation to obtain a modifier;

[0066] S2. Add 1 g of chitosan to a mixed solution of 100 mL of acetic acid and toluene (the mass fraction of acetic acid is 24%), stir until completely dissolved, then add 2.4 g of a modifier and 15 mL of dicyclohexylcarbodiimide, control the reaction temperature to 60°C, keep the reaction warm for 12 hours, and after the reaction is complete, distill under reduced pressure, wash with ethanol and water in turn, and dry in an oven to obtain modified chitosan.

[0067] Example 5

[0068] A1. Dissolve 18 g of modified chitosan in 100 g of citric acid solution (mass fraction 12%) and stir for 0.5 h to mix evenly. Add 3 g of cobalt chloride hexahydrate and 4 g of ferric chloride hexahydrate and continue stirring for 0.5 h to obtain a mixed solution.

[0069] A2, placing the mixed solution obtained in step A1 in a constant temperature water bath at 80°C, stirring until the liquid is evaporated, then scraping out a sample and drying it in a vacuum oven at 80°C for 6 hours to obtain a mixed solid;

[0070] A3, adding the mixed solid obtained in step A2 into a porcelain boat, and placing the whole in a tube furnace, and introducing argon gas, heating to 600°C at a heating rate of 2°C / min, calcining for 2h, after the calcination is completed, waiting for the tube furnace to cool naturally to room temperature, soaking the product in a hydrochloric acid solution (mass fraction 12%) for stirring and pickling, then washing with ultrapure water for several times until the filtrate is neutral, and then washing with anhydrous ethanol for 3 times, and finally drying in a vacuum oven at 80°C for 6h to obtain a nano Co2O3 / Fe3O4 composite PMS activated catalyst;

[0071] Wherein, the modified chitosan is prepared by the following steps:

[0072] S1. In a three-necked flask equipped with a stirring device, 18.4 g of 2,5-thiophene dicarboxylic acid, 9.4 g of 4-aminopyridine, 20.6 g of dicyclohexylcarbodiimide and 100 mL of toluene were stirred and mixed uniformly, and then placed in a water bath at 55° C. and heated in a water bath for 6 h. After the reaction was completed, the mixture was filtered, and the solvent was removed by distillation under reduced pressure. The mixture was purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 2:3), and the eluent was removed by rotary evaporation to obtain a modifier;

[0073] S2. Add 1 g of chitosan to a mixed solution of 100 mL of acetic acid and toluene (the mass fraction of acetic acid is 24%), stir until completely dissolved, then add 2.4 g of a modifier and 15 mL of dicyclohexylcarbodiimide, control the reaction temperature to 60°C, keep the reaction warm for 12 hours, and after the reaction is complete, distill under reduced pressure, wash with ethanol and water in turn, and dry in an oven to obtain modified chitosan.

[0074] 2 mM permonosulfate was added to 50 mL of a Rhodamine 6G (R6G) solution with an initial concentration of 50 mg / L. After stirring, 10 mg of the catalyst prepared in Examples 1-5 was added to the above solution respectively, and the degradation experiment was carried out by stirring. 2 mL of the sample was taken at regular intervals, and 20 μL of a 1 M sodium sulfate (Na2SO4) solution was added to the sample to terminate the degradation reaction. The R6G concentration in the sample was then measured using an ultraviolet spectrophotometer; degradation rate (%) = (R6G initial concentration - R6G concentration after degradation) / R6G initial concentration × 100%.

[0075] The measured degradation rates are shown in Table 1:

[0076] Table 1

[0077]

[0078]

[0079] According to the degradation rate test results of R6G of Examples 1-5 in Table 1, Figure 6 The degradation curve and Figure 7 It can be seen from the change graph of the recycling degradation efficiency that the nano Co2O3 / Fe3O4 composite PMS activation catalyst obtained by the preparation method of all embodiments of the present application shows excellent catalytic performance and magnetism, among which the degradation rate of Example 1 is as high as 96.8%, and the magnetism is as high as 29.8emu / g. After 5 cycles of use, the degradation rate is still as high as 93.2%. It is worth mentioning that the catalysts prepared in all embodiments can degrade R6G by more than 85% within 1 minute, which proves the high efficiency and high stability of the catalyst; therefore, the catalyst prepared by the present invention has a very high activation efficiency for PMS, and can be recovered by magnetic force, which has significant application value in the water treatment industry.

[0080] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0081] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a nano Co2O3 / Fe3O4 composite PMS activated catalyst, characterized in that: The following steps are involved: A1. Dissolve the modified chitosan in a citric acid solution and stir to mix evenly, add cobalt chloride hexahydrate and ferric chloride hexahydrate, and continue stirring to mix to obtain a mixed solution; A2, placing the mixed solution obtained in step A1 in a constant temperature water bath, stirring until the liquid is evaporated, and then scraping out the sample and drying it to obtain a mixed solid; A3. Add the mixed solid obtained in step A2 into a porcelain boat, place the whole in a tube furnace, introduce inert gas, and calcine. After the calcination is completed, wait for the tube furnace to cool naturally to room temperature, soak the product in a hydrochloric acid solution for stirring and pickling, then wash to neutrality, wash again, and finally dry to obtain a nano Co2O3 / Fe3O4 composite PMS activated catalyst.

2. The method for preparing a nano-Co2O3 / Fe3O4 composite PMS activated catalyst according to claim 1, characterized in that: The modified chitosan is prepared by the following steps: S1. After 2,5-thiophenedicarboxylic acid, 4-aminopyridine, dicyclohexylcarbodiimide and toluene are stirred and mixed evenly, the mixture is heated at 55° C. for 6 h. After the reaction is completed, the mixture is filtered, distilled under reduced pressure, purified by column chromatography, and rotary evaporated to obtain a modifier; S2. Add chitosan to a mixed solution of acetic acid and toluene, stir until completely dissolved, then add a modifier and dicyclohexylcarbodiimide, react at 60° C. for 12 h, and after the reaction is completed, distill under reduced pressure, wash, and dry to obtain modified chitosan.

3. The method for preparing a nano-Co2O3 / Fe3O4 composite PMS activated catalyst according to claim 2, characterized in that: In step S1, the ratio of 2,5-thiophenedicarboxylic acid, 4-aminopyridine, dicyclohexylcarbodiimide and toluene is 18.4 g: 9.4 g: 20.6 g: 100 mL.

4. The method for preparing a nano-Co2O3 / Fe3O4 composite PMS activated catalyst according to claim 2, characterized in that: In step S2, the ratio of the mixed solution of acetic acid and toluene, chitosan, modifier, and dicyclohexylcarbodiimide is 100 mL: 1 g: 2.4 g: 15 mL.

5. The method for preparing a nano-Co2O3 / Fe3O4 composite PMS activated catalyst according to claim 1, characterized in that: The raw materials are calculated in parts by weight as follows: 18-36 parts of modified chitosan, 100-200 parts of citric acid solution, 3-7 parts of cobalt chloride hexahydrate, and 4-8 parts of ferric chloride hexahydrate.

6. The method for preparing a nano-Co2O3 / Fe3O4 composite PMS activated catalyst according to claim 1, characterized in that: The calcination conditions in step A3 are to increase the temperature to 600-800° C. at a heating rate of 2° C. / min and keep the temperature for 2-5 hours.

7. The method for preparing a nano-Co2O3 / Fe3O4 composite PMS activated catalyst according to claim 1, characterized in that: The inert gas in step A3 is one of nitrogen and argon.

8. A nano Co2O3 / Fe3O4 composite PMS activated catalyst, characterized in that: Prepared according to the method according to any one of claims 1 to 7.

9. The nano-Co2O3 / Fe3O4 composite PMS activated catalyst according to claim 8, characterized in that: Application in water treatment field.

Citation Information

Patent Citations

  • Bimetal-supported composite catalyst and method for catalytic synthesis of p-aminophenylacetylene by utilizing the same

    CN110882723A

  • Preparation method and application of ferrocobalt alloy magnetic chitosan carbonized microspheres

    CN112206826A

  • High-phosphorus-content chitosan derivative, preparation thereof and application of the high-phosphorus-content chitosan derivative in loading nano zero-valent iron

    CN113185622A

  • Metal / nitrogen-doped porous carbon catalyst for treating organic wastewater and preparation method thereof

    CN113559914A

  • CoFe2O4-WTRs Composite Magnetic Catalyst, Preparation Method and Application Thereof

    US20200238268A1